INTERNATIONAL INVESTMENT POSITION OF UKRAINE IN CRISIS CONDITIONS - BIDA, Marianna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the study of the impact of crisis phenomena on the volume of foreign direct investment (FDI) in Ukraine. In the context of global economic dynamics and the interconnection of international markets, the role of FDI in ensuring sustainable economic growth is analyzed and their importance for the country's development is revealed (based on the GDP indicator). Variants are given that reflect the dependence between crisis phenomena and the volume of foreign direct investments. The indicators published on the World Bank's website and used at the international level to assess net inflows and net outflows of foreign direct investments are described. The correlation of the dynamics of changes in the analyzed indicators of Ukraine against the background of changes in similar indicators of the EU countries and the world is visually presented for the studied period of 1994-2022, which made it possible to conclude the nature of crisis phenomena that influenced the change in the trend. The results of the study provided a general idea of the negative impact of crisis phenomena on the dynamics of foreign direct investment. The analysis made it possible to single out external (international, global) and internal crisis phenomena. External crisis phenomena (the global financial crisis of 2008-2009; the spread of the COVID-19 pandemic in 2020-2021) took place in many countries of the world and the European Union and caused a decrease in FDI due to economic recession, financial uncertainty, reduced availability of capital, uncertainty in business environments. Internal crisis phenomena were related to the economy and politics conducted in Ukraine, as well as caused by the military conflict with Russia (the Russian annexation of Crimea, the military conflict in the East of Ukraine, the full-scale Russian invasion of Ukraine on February 24, 2022, the Russian-Ukrainian war), which created uncertainty, risks and negative conditions for investing in Ukraine. The conclusions of the article are aimed at emphasizing the importance of understanding the mechanisms of the impact of crisis phenomena on FDI and the need to develop strategies to ensure stability and sustainable growth of FDI in conditions of uncertainty and the negative impact of external and internal factors.
Keywords: international investment position; foreign direct investment; GDP; crisis conditions; global financial crisis; COVID-19 pandemic; political instability; economic instability; military conflict; Russian-Ukrainian war